Independent Majelis Disiplin Profesi Ensures Legal Certainty in Health Law: Majelis Disiplin Profesi yang Independen Menjamin Kepastian Hukum dalam Hukum Kesehatan - Dzulqarnain Andira (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Indonesia’s health legal system has introduced a dedicated professional discipline mechanism through the Majelis Disiplin Profesi (MDP) under Law Number 17 of 2023 on Health. Specific Background: Articles 304–309 position MDP as the initial forum to examine alleged breaches of medical and health professional discipline prior to criminal investigation, reflecting a quasi-judicial role within health governance. Knowledge Gap: The statutory design raises unresolved concerns regarding guarantees of institutional autonomy and protection from executive intervention, despite the direct significance of MDP recommendations for subsequent criminal and civil processes. Aims: This study articulates the urgency of structural independence for MDP by mapping its juridical position, independence dimensions (institutional, functional, and administrative), and normative risks within the lex specialis framework for medical disputes. Results: The analysis identifies that insufficient independence may generate legal uncertainty, weaken objectivity of recommendations, and risk constraining constitutional access to justice, including tensions with equality before the law, while also creating overlap risks with the general judiciary if recommendations are treated as an absolute procedural prerequisite. Novelty: The article synthesizes MDP’s quasi-judicial character with a three-dimensional independence model to assess the feasibility of lex specialis discipline mechanisms under the 2023 Health Law. Implications: Strengthening MDP’s institutional design and ensuring transparent examination procedures are positioned as priority measures to sustain professional accountability, balanced protection for patients and health workers, and public trust in disciplinary adjudication. Highlights: The disciplinary mechanism is placed as the initial examination stage before investigative procedures begin. Autonomy deficits are linked to risks of non-objective recommendations and constrained access to justice. Treating council recommendations as an absolute procedural gate may create overlap with general adjudication. Keywords:Professional Discipline Council, Health Law 2023, Institutional Independence, Quasi-Judicial Body, Lex Specialis